2023
DOI: 10.3389/fpls.2023.1101611
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient-mediated modulation of flowering time

Abstract: Nutrition affects plant growth and development, including flowering. Flowering represents the transition from the vegetative period to the reproduction period and requires the consumption of nutrients. Moreover, nutrients (e.g., nitrate) act as signals that affect flowering. Regulation of flowering time is therefore intimately associated with both nutrient-use efficiency and crop yield. Here, we review current knowledge of the relationships between nutrients (primarily nitrogen, phosphorus, and potassium) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…These genes participate in the metabolic process of carbohydrates, increasing the content of soluble sugars in leaves and therefore providing nutrients and energy for plant growth, development and flowering. Additionally, nitrogen sources are thought to play a crucial role in plant developmental processes, including the regulation of flowering time (Zhang et al, 2021;Zhang et al, 2023). Our study showed that the CEPRECEPTOR1 (CEPR1) gene, which is involved in nitrate absorption and signal transduction (Ota et al, 2020;Taleski et al, 2020), was downregulated and reduced nitrogen source substances in oat, resulting in early flowering under a long-day photoperiod.…”
Section: Figurementioning
confidence: 78%
“…These genes participate in the metabolic process of carbohydrates, increasing the content of soluble sugars in leaves and therefore providing nutrients and energy for plant growth, development and flowering. Additionally, nitrogen sources are thought to play a crucial role in plant developmental processes, including the regulation of flowering time (Zhang et al, 2021;Zhang et al, 2023). Our study showed that the CEPRECEPTOR1 (CEPR1) gene, which is involved in nitrate absorption and signal transduction (Ota et al, 2020;Taleski et al, 2020), was downregulated and reduced nitrogen source substances in oat, resulting in early flowering under a long-day photoperiod.…”
Section: Figurementioning
confidence: 78%
“…Fertilizers and plant nutrient solutions are applied as a common practice to alleviate abiotic stress and enhance crop yield [ 3 , 8 , 9 ]. Recently, nutrient deficiency (references in [ 10 , 11 , 12 ]), imbalance of nutrients [ 13 , 14 , 15 , 16 ], and heavy metal accumulation in soil [ 17 , 18 ] have been reported to influence flowering time [ 8 ], leading to altered plant growth.…”
Section: Introductionmentioning
confidence: 99%
“…The deficiency or imbalance of three major and primary nutrients, nitrogen (N), phosphorus (P), and potassium (K), results in altered flowering time in plants [ 10 ]. Previously, NPK fertilizers have been used to control flowering time in crop plants [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations